Crack shape evolution and stress intensity factors for opposite surface cracks in aircraft shaft under tension and combined loading. Issue 2 (1st February 2023) - Suresh Kumar, S.; Shyam Sundar, Arjun; Deepak, R.
Abstract: Stress Intensity Factor (SIF) of opposite surface cracks presented in an un-notched round bar has been determined under tension and combined load conditions. The influence of loading modes on SIF of opposite surface cracks has been attempted using numerical method. Crack depth ratio [(a/d); 'a' crack depth and 'd' diameter of the bar] ranging 0.1 to 0.4 and crack aspect ratio [(a/c); 'a' crack depth and 'c' semi major axis of the ellipse] ranging 0.2 to 1.0 were considered. Mixed mode SIF was calculated with consideration of mode-II and mode-III fractures. When the bar was subjected to pure tensile loading, as the crack depth ratio (a/d) increases, a crossover (higher SIF value changes from middle region to surface region) in SIF distribution was observed for an aspect ratio of 0.6. This implies that the growing crack has changed its propagation behavior as the depth ratio increases. In addition to tension, when torque was applied, nonuniform and asymmetric SIF spread was observed for semi elliptic crack [(a/c) = 0.2] compared to semi-circular [(a/c) = 1.0] crack. It was also noted that mode-I fracture is higher at the middle region [P/P0 = 0] of the rack border, whereas mode-II and mode-III fracture is higher at the crack surface region [P/P0 = ±1]. Due to combined loading, more influence of mode-II and mode-III fracture failure was observed and their effect is marginal at the middle region [P/P0 = 0] of the crack border. Using surface plots, SIF of opposite cracks located in un-notched round bar has been determined.